Analysis of the sustainability of cities that incorporate the human dimension: study in the city of Queimadas-PB (Polis (Santiago), 2020)
This study aims to incorporate the human dimension in the analysis of the sustainability of cities, in the city of Queimadas-PB, based on the dimensions of the living, safe, healthy and sustainable city listed by Gehl (2015). The research is characterized by being descriptive, given the images collected; exploratory, considering the explored locations of the city under study; qualitative, considering that the information obtained helped in the construction of the indicators. The bibliographical research, necessary for the writing of this field research as a tool of knowledge of the environment under study, helped in the collection of data. Regarding the information collected, we verified that in the city of Queimadas - PB, there are still problems that interfere negatively in its development, within the aspects of the city being alive, safe, healthy and sustainable, needing more incisive public policies that can value more the context of the people, going beyond the physical structure, which can contribute to a lifestyle with better quality in conjunction with the environment.
Keywords: Urban sustainability; sustainability indicators; urban planning; sustainable city